2012
DOI: 10.1007/s10549-012-2104-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific transcriptional response of four blockers of estrogen receptors on estradiol-modulated genes in the mouse mammary gland

Abstract: Novel agents for the endocrine therapy of breast cancer are needed, especially in order to take advantage of the multiple consecutive responses observed in metastatic progressing breast cancer following previous hormone therapy, thus delaying the use of cytotoxic chemotherapy with its frequent poor tolerance and serious side effects. Acolbifene (ACOL) is a novel and unique antiestrogen which represents a unique opportunity to achieve the most potent and specific blockade of estrogen action in the mammary gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 99 publications
2
9
1
Order By: Relevance
“…This finding is consistent with the large increase of lobuloalveolar differentiation found in these animals (18), suggesting a soy promotional effect on breast differentiation through menarche. There was also a trend of lower GATA-3 with soy following menarche, which was consistent with the pattern of ERα and GREB1 mRNA and a study in ovariectomized mice that showed downregulation of GATA-3 expression through ER modulation induced by exogenous estrogen (49). …”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with the large increase of lobuloalveolar differentiation found in these animals (18), suggesting a soy promotional effect on breast differentiation through menarche. There was also a trend of lower GATA-3 with soy following menarche, which was consistent with the pattern of ERα and GREB1 mRNA and a study in ovariectomized mice that showed downregulation of GATA-3 expression through ER modulation induced by exogenous estrogen (49). …”
Section: Discussionsupporting
confidence: 87%
“…RBP7 has been shown to be up-regulated in IPF lung tissue [71] and in wound tissue in the normal chicken chorioallantoic wound model [72] although its role in fibrosis is unclear. RBP7 is positively regulated by E2 in breast cancer cells [73] and mouse mammary gland [74]. The discrepancy in regulation in our study may be a result of variable exposure dynamics as the study by Calvo et al exposed mice to one dose of E2 and sacrificed the animals 3 h later [74] while we exposed cells in vitro for 24 h. Nonetheless, E2 appears to regulate RBP7 which may exhibit an unexplored effect on fibrogenic signaling.…”
Section: Discussionmentioning
confidence: 78%
“…There was no clear effect on the chemokine stromal cell-derived factor 1 (SDF-1) which is important for viability of stem cells and has been implicated in ligand-independent phosphorylation of the estrogen receptor and tamoxifen resistance [3739] Tamoxifen has been variably associated with increases in SDF-1 [34, 40, 41]. A recent report assessing the short term effects of several SERMs and fulvestrant on a large number of genes in mammary cancer from ovariectomized mice suggests that acolbifene reverses the effect of estradiol on more estrogen inducible genes than tamoxifen, raloxifene, or fulvestrant [42]. …”
Section: Discussionmentioning
confidence: 99%